2009
DOI: 10.1111/j.1600-0404.1999.tb00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical characteristics of myasthenia gravis in Belgrade, Yugoslavia (1983-1992)

Abstract: This is the first epidemiological study of myasthenia gravis (MG) in the area of Belgrade. During the survey period (1983–1992), 124 incidental cases of MG were observed, producing an average annual incidence rate of 7.1 per million population (women, 8.3; men, 5.8). Age and sex specific incidence rates for females demonstrated a bimodal pattern, with the first peak in the age group between 20 and 40, and the second peak in the age group 70–80. The age‐specific rates for males showed unimodal pattern, reaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 29 publications
3
23
0
1
Order By: Relevance
“…Patients with thymoma had an older age of onset of symptoms, but there were no gender differences. These data are similar to those reported by Lavrnic et al 30 .…”
Section: Treatment Proceduressupporting
confidence: 82%
“…Patients with thymoma had an older age of onset of symptoms, but there were no gender differences. These data are similar to those reported by Lavrnic et al 30 .…”
Section: Treatment Proceduressupporting
confidence: 82%
“…The studied area in the Netherlands is characterized by a high population density and urbanity, with large cities and an airport. Two recent studies examining the geographical variation have found more prevalent MG cases in the urban areas compared to the rural areas [2,45] . One could speculate whether the urban differences reflect individual behavior or exposure of exogenous environmental factors like, for example, air pollution influencing the disease development.…”
Section: Discussionmentioning
confidence: 99%
“…Ten investigations used census or other national statistics data for their denominator [21,22,24,27,29,31,36,39,40,43] , one did not give any denominator data [13] and the others provided denominator estimates but did not give their source. Overestimation of incidence rates was thought to be unlikely where specialists diagnosed or reviewed the cases included [14, 16, 18, 19, 24-27, 29, 32, 36, 37] ; other studies reported reliable case identification [40] , using a 3-year follow-up period to ensure correct diagnosis [23] and a regular clinical follow-up to exclude questionable cases [13] .…”
Section: Accuracy Of Ratesmentioning
confidence: 99%
“…The main causes of missing cases in the studies were mild symptoms or cases being diagnosed and managed in primary care but the case finding strategy of the incidence study only including secondary care records [16-18, 20-25, 27, 30, 37, 40, 41] , death before a diagnosis was made [17,21,22,27,42] and misdiagnosis [36,42] [21,38,40] only included patients who were seropositive for antiAChR antibodies, which will have underestimated the incidence rates by about 15% [1,4,40] . Ten investigations used census or other national statistics data for their denominator [21,22,24,27,29,31,36,39,40,43] , one did not give any denominator data [13] and the others provided denominator estimates but did not give their source.…”
Section: Accuracy Of Ratesmentioning
confidence: 99%